Eliciting tacit knowledge from special education teachers - Ghazali, Norsyahida; Abdul Rahman, Azizah; Bahari, Mahadi (2012)
Children are national precious asset whether they are normal or special.In this paper special children refer to children with learning disability.Children with learning disability usually have problem in understanding instruction during their learning process.Therefore, they require experienced and well trained teacher to teach them because they can deal with their special needs and ability.However,the valuable knowledge on how to teach these children usually remains tacitly in the mind of the teachers.Therefore, this paper tries to elicit tacit knowledge from special education teachers for the purpose of knowledge sharing. Storytelling and scenario method were used to capture the tacit knowledge from five special education teachers.As a result,tips on effective teaching has been identify based on the situation.The result can be shared among new teachers,researchers and also can be consider in designing courseware for children with learning disability.